The Role of The Company Life Cycle on Chief Executive Officer Power and Earnings Management - Akhmad Sigit Adiwibowo; Putri Nurmala (Accounting Analysis Journal, 2023)
Purpose : This study aims to re-examine whether chief executive officer (CEO) power affects earnings management and whether company life cycles can moderate the effect of CEO power on earnings management. Method : This study used publicly listed companies in the Indonesia Stock Exchange period 2017-2021, are 74 companies, or 370 data, were picked using a purposive sampling method that eliminates companies with outliers. This research uses panel data regression with a random effect model to examine CEO power on earnings management with the company’s life cycle as moderating variables. Findings : This study finds that CEO power does not affect earnings management, and the decline stage can moderate the effect of CEO power on earnings management. However, the introduction, growth, and mature stage cannot moderate the effect of CEO power on earnings management. Novelty : This study contributes to the literature on earnings management by highlighting CEO power in Indonesian companies with different life cycles. This study provides a unique perspective on earnings management, especially in emerging markets like Indonesia. Keywords : CEO’s Power, Earnings Management, Company Life Cycle